The Princeton companion to Jonathan Edwards - Lee, Sang Hyun, 1938- (Princeton University Press, 2020)
Jonathan Edwards (1703-1758) is widely recognized as one of the greatest philosopher-theologians America has ever produced, and recent years have seen a remarkable increase in research on his writings. To date, however, there has been no single authoritative volume that introduces and interprets the key aspects of Edwards' thought as a whole. The Princeton Companion to Jonathan Edwards provides just such a concise and comprehensive work, one that will be invaluable to students and scholars of American religion and theology as well as of literature, philosophy, and history.Comprising twenty essays by leading scholars on Edwards, the book will inform and challenge readers on subjects ranging from Edwards' understanding of the Trinity, God and the world, Christ, and salvation, as well as of history, typology, the church, and mission to Native Americans. It also includes a chronology of Edwards' life and writings that incorporates current research. Those familiar with Edwards' writings will find in these essays succinct expositions as well as bold new interpretations, and others will find an accessible, authoritative, up-to-date orientation to his multifaceted thought. The essays are by Robert E. Brown, Allen C. Guezlo, Robert W. Jenson, Wilson H. Kimnach, Janice Knight, Sang Hyun Lee, Gerald R. McDermott, Kenneth P. Minkema, Mark Noll, Richard R. Niebuhr, Amy Plantinga Pauw, John E. Smith, Stephen J. Stein, Harry S. Stout, Douglas A. Sweeney, Peter J. Thuesen, and John F. Wilson.